VD_FINDINFO APG 32/11 - 11/2013 vom 19. August 2013 - VD Tribunal cantonal (2013)
APG, RESTITUTIONEN GÉNÉRAL, PÉREMPTION, PROTECTION CIVILE | 1a al. 3 LAPG, 21 LAPG, 23 LAPG, 25 LPGA, 28 LPPCi, 35 LPPCi, 36 LPPCi, 75 LPPCi, 7 OIPCC, 41 al. 3 OPCi